Analisis Pemberian Insentif Pemungutan Pajak Bumi dan Bangunan Sektor Pedesaan dan Perkotaan Setelah Menjadi Pajak Daerah (Studi Pada Dinas Pendapatan Daerah Kabupaten Tulungagung) - Yuda, Saifulloh Puspa (Jurnal Mahasiswa Perpajakan, 2015)
The  delegation is conducted or modified based on fiscal decentralization. Act No. 8 of 2009 about Local Tax and Local Retribution is the indication of new era for the management of PBB P-2.  A mandatory tenet in this Act is to delegate the management of PBB P-2  to local government. The consequence of PBB P-2 localization is that the local is not anymore accepting donation from central government, and therefore, the fee of the collection task, which is that 9 % of the proceed is given by central government to the  collecting officer, is not anymore prevailed.Research type is descriptive with qualitative approach. Result of this research indicates that the impact of PBB P-2 localization into local tax is evident through the change of the collecting fee into 5 % col lection incentive. The nominal of collection incentive is indeed smaller than collecting fee. Incentive treatment is aimed to give a reward, as additional income, to the collection officers for their performance. Incentive treatment may also be useful as stimulant or motivation for the tax collector officers to improve their performance and al so to increase the revenue.Keywords: Collection Incentive, Collector Officer, PBB P-2